A predictive model for patent ductus arteriosus seven days postpartum in preterm infants: an ultrasound-based assessment of ductus arteriosus intimal thickness within 24 h after birth - Hu, Xin-Lu; Zhu, Ting-Ting; Wang, Hui; Hou, Cui; Ni, Jun-Cheng; Zhang, Zhuo-Fan; Li, Xiao-Chen; Peng, Hao; Li, Hong; Sun, Ling; Xu, Qiu-Qin (Frontiers in Pediatrics, 2024)
The final predictive model included birth weight, application of mechanical ventilation, left ventricular end-diastolic diameter (LVEDd), LD, and the logarithm of IT (logIT). The receiver operating characteristic (ROC) curve for the model, predicated on logIT, exhibited excellent discriminative power with an area under the curve (AUC) of 0.985 (95% CI: 0.966-1.000), sensitivity of 1.000, and specificity of 0.909. Moreover, the model demonstrated robust calibration and goodness-of-fit (chi-square value=0.560, p>0.05), as well as strong reproducibility (accuracy: 0.935, Kappa: 0.773), as evidenced by 10-fold cross-validation. A decision curve analysis confirmed the model's broad clinical utility.Our study successfully establishes a predictive model for PDA in preterm infants at seven days postpartum, leveraging the measurement of DA IT. This model enables identifying, within the first 24 hours of life, infants who are likely to benefit from timely DA closure, thereby informing treatment decisions.